Does breathing disturb coordination in butterfly? - Seifert, L.; Chollet, D.; Sanders, R. (International Journal of Sports Medicine, 2010)
This study quantified the effects of breathing compared to non-breathing and "race pace" on arm to leg coordination in the butterfly stroke. Twelve elite male swimmers swam at four paces: 400 m, 200 m, 100 m and 50 m. The arm and leg stroke phases were identified by video analysis to calculate the total time gap (TTG), which is the sum of T1 (hands' entry in the water/high point of first kick), T2 (beginning of the hands' backward movement/low point of first kick), T3 (hands' arrival in a vertical plane to the shoulders/high point of second kick) and T4 (hands' release from the water/low point of second kick). Two strokes with breathing were compared to two strokes with breath-holding. The TTG was greater with breathing (23.3% vs. 19%), showing less propulsive continuity between arm and leg actions (p<0.05). This was due to the shorter downward leg kick and longer arm catch and upward leg kick that led to longer glide time. Conversely, breathing leads to greater coupling between the hand exit and the end of leg propulsion, which was due to a shorter arm push phase to facilitate the head exit to breathe.